2017
DOI: 10.18203/2319-2003.ijbcp20175535
|View full text |Cite
|
Sign up to set email alerts
|

The correlation of cardiovascular risk factors and angiographic findings with serum vitamin D levels in patients undergoing coronary angiography

Abstract: INTRODUCTIONVDD is now a pandemic cutting across age groups, ruralurban divide and developing or developed countries. . Vit-D level <20ng/ml i.e. Vit-D deficiency (VDD) in 68, 20-30ng/ml i.e. Vit-D insufficiency (VDI) in 22 and >30ng/ml (normal) in 10. VDD was profound in 51-60 and 61-70 years age groups. Statistical correlation of VDD was not significant with conventional risk factors, but statistically significant correlation of VDD was observed with dyslipidemia and CAG findings in our study. Conclusions: L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Several other studies detected an inverse signi cant correlation between vitamin D level and Gensini score [34]. A study by Tripathy et al showed that reducing serum vitamin D levels will increase the number of patients with single, two, and three-vessel coronary artery disease [35]. It might be attributed to the protective role of 25-OH vitamin D, the active form of vitamin D, which regulates calcium metabolism and effectively maintains the regular role of cardiovascular systems and vascular health [7,36].…”
Section: Discussionmentioning
confidence: 99%
“…Several other studies detected an inverse signi cant correlation between vitamin D level and Gensini score [34]. A study by Tripathy et al showed that reducing serum vitamin D levels will increase the number of patients with single, two, and three-vessel coronary artery disease [35]. It might be attributed to the protective role of 25-OH vitamin D, the active form of vitamin D, which regulates calcium metabolism and effectively maintains the regular role of cardiovascular systems and vascular health [7,36].…”
Section: Discussionmentioning
confidence: 99%